Perbandingan Keefektifan Kompres Tepid Sponge Dan Kompres Air Hangat Terhadap Penurunan Suhu Tubuh Pada Anak Demam Tifoid Dengan Hipertermi Di Rsud Sukoharjo - Keliobas, Ali Ahmad; , Supratman, SKM., M.Kes., Ph.D; , Dian Nur W, S.Kep., Ns (2016)
Typhoid fever is one of the diseases of the digestive that is caused by the salmonella typhi and characterized by a rise in body temperature or fever. Compress is one of the measures to decrease the production of heat and heat increase spending. The purpose of this research is viewed comparison of effectiveness between tepid sponge compress and warm water compress against a decrease in body temperature. Types of quantitative research, research design used was a quasi experimental design with pretest-posttest two group treatment. Sample research amounted to 38 respondents, then divided in two groups of treatment tepid sponge compress and warm water compress so that each group of 19 respondents, treatment was given for 15 minutes. Statistical analysis using the T-Test test : Paired Sample T-Test to analyze the pre-test and post-test both treatment groups and Independent Sample T-Test to analyze the effectiveness of the comparison between the two treatment groups. Results Paired Sample T-Test, the significant value or p-value of tepid sponge compress for 0.000, the mean pre-test 38.6110c and post-test 36.8890c or decreased body temperature 1.720c and the significant value or p-value of warm water compress for 0.000, the mean pre-test 38.5000c and post-test 37.3790c or decreased body temperature 1.120c. Concluded both techniques are effective compress against a decrease in body temperature, but tepid sponge compress is more effective to decrease body temperature. The result of Independent Sample T-Test, the significant value or p-value of 0.001. Statistical analysis has shown no significant effectiveness comparison between tepid sponge compress and warm water compress against the drop in body temperature the children with hyperthermia typhoid fever at RSUD Sukoharjo. Key Word : Tepid Sponge Compress And Warm Water Compress, Body Temperature, Typhoid Fever.